Riding the FinTech Wave: Exploring Service Satisfaction and Trust among Generations Y and Z - Daisy Mui Hung Kee; Yi Ling Kum; Jia Hee Lee; Ngee Cheng Lee; Xin Ting Lee; Daman Singh Muckar (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
Financial technology, or FinTech, is revolutionizing banking worldwide by introducing innovative services. However, clients' comprehension and willingness to embrace or adapt to new technologies remain uncertain. As FinTech continues to disrupt traditional banking procedures, it is critical to investigate how these innovations affect Generation Y and Z's perceptions of service satisfaction. As a result, the objective of this study is to determine the major characteristics that impact client satisfaction and trust in the use of FinTech-based services. Data from 250 respondents who use FinTech services show that User Trust and User Satisfaction are important for them when adopting FinTech. The results indicate that security, privacy, ease of use, and convenience are the key factors positively influencing user trust and satisfaction in FinTech services, with a reciprocal relationship between trust and satisfaction. This symbiotic relationship highlights the importance for FinTech companies to prioritize both customer satisfaction and trust-building initiatives to foster long-term relationships with their users.